Partial productivity and technical efficiency of small and medium enterprises in the Malaysian food processing industry - Shamsudin, Mad Nasir; Yodfiatfinda,; Radam, Alias; Yusop, Zulkornain (Universiti Putra Malaysia Press, 2013)
The objective of this study is to investigate the partial productivity and technical efficiency (TE) of small and medium enterprises (SMEs) in the Malaysian food processing industry. A non-parametric approach data envelopment analysis (DEA) was employed on panel data of 35 sub-industries during the period 2000 to 2006. The result shows that capital productivity was relatively unchangedand material productivity shows a declining trend during the period of observation. In 2000, material productivity (value added per material) was recorded at 0.22, and it stood at 0.18 in 2006. Higher cost of labor was found in the manufacturing of alcohol, palm oil, refined palm oil, palm kernel oil, and sauce . Five sub-industries were technically efficient (TE is equal to unity) during the estimation periods. These industries are refined palm oil, kernel palm oil, feed, alcohol and soft drink. In contrast, five sub-industries experienced lower TE: canning of pineapple, sugar, glucose, coconuts and other flour, with the TE scores varying between 35.9 percent up to 48.1 percent. Labor cost and labor productivity increased from 13.65 to 13.95.